Ventilation Optimization Based on Spatial-Temporal Distribution and Removal Efficiency of Patient-Exhaled Pollutants in Hospital Wards During the Post-Epidemic Period - Min Chen; Qingyu Wang (Buildings)
Given the potential risks of unknown and emerging infectious respiratory diseases, prioritizing an appropriate ventilation strategy is crucial for controlling aerosol droplet dispersion and mitigating cross-infection in hospital wards during post-epidemic periods. This study optimizes the layout of supply diffusers and exhaust outlets in a typical two-bed ward, employing a downward-supply and bottom-exhaust airflow pattern. Beyond ventilation, implementing strict infection control protocols is crucial, including regular disinfection of high-touch surfaces. CO2 serves as a surrogate for exhaled gaseous pollutants, and a species transport model is utilized to investigate the airflow field under various configurations of vents. Comparisons of CO2 concentrations at the respiratory planes of patients, accompanying staff (AS), and healthcare workers (HCWs) across nine cases are reported. A discrete phase model (DPM) is employed to simulate the spatial-temporal dispersion characteristics of four different particle sizes (3 μm, 12 μm, 20 μm, and 45 μm) exhaled by the infected patient (Patient 1) over 300 s. Ventilation effectiveness is evaluated using indicators like contaminant removal efficiency (CRE), suspension rate (SR), deposition rate (DER), and removal rate (RR) of aerosol droplets. The results indicate that Case 9 exhibits the highest CRE across all respiratory planes, indicating the most effective removal of gaseous pollutants. Case 2 shows the highest RR at 50.3%, followed by Case 1 with 40.4%. However, in Case 2, a significant portion of aerosol droplets diffuse towards Patient 2, potentially increasing the cross-infection risk. Balancing patient safety with pollutant removal efficacy, Case 1 performs best in the removal of aerosol droplets. The findings offer novel insights for the practical implementation of ventilation strategies in hospital wards, ensuring personnel health and safety during the post-epidemic period.